Neuroprognostication for Patients with Amyotrophic Lateral Sclerosis: An Updated, Evidence-Based Review - Martin Schaff, Christina; Kurent, Jerome E.; Kolodziejczak, Sherry; Milic, Michelle; Foster, Laura A.; Mehta, Ambereen K. (Seminars in Neurology, 2023)
Amyotrophic lateral sclerosis (ALS) is a rapidly progressive neurodegenerative disorder that presents and progresses in various ways, making prognostication difficult. Several paradigms exist for providers to elucidate prognosis in a way that addresses not only the amount of time a patient has to live, but also a patient's quality of their life moving forward. Prognostication, with regard to both survivability and quality of life, is impacted by several features that include, but are not limited to, patient demographics, clinical features on presentation, and over time, access to therapy, and access to multidisciplinary clinics. An understanding of the impact that these features have on the life of a patient with ALS can help providers to develop a better and more personalized approach for patients related to their clinical prognosis after a diagnosis is made. The ultimate goal of prognostication is to empower patients with ALS to take control and make decisions with their care teams to ensure that their goals are addressed and met.
Keywords: ALS; prognosis; quality of life; palliative care; multidisciplinary clinic